Astroquímica e astrobiologia no curso de licenciatura em ciências biológicas: reflexões e propostas de aplicação - Reis, Luis Eduardo Matos (2024)
This work aims to present teaching proposals for Chemistry concepts in Higher Education through its interface with Astrochemistry and Astrobiology. The research took place within the General Chemistry and Organic Chemistry courses of the Bachelor's Degree in Biological Sciences at the Baiano Federal Institute, Serrinha Campus. The research aims to enrich the academic training of students, both from a scientific and pedagogical perspective, by promoting broader, interdisciplinary, and contextualized teaching. The educational product associated with this work is an e-book entitled "Guide to Astrochemistry and Astrobiology Activities in Higher Education," resulting from activities developed in two Didactic Sequences, applied in different classes, which make use of various pedagogical tools such as molecular modeling kits, computational chemistry, and spectroscopic analysis, with the aim of developing different skills in students. As a result of the research, we hope that the appropriation of the main Chemistry concepts in the training of students in Biological Sciences and related areas will be significant, and that equipping them with basic knowledge of Astrochemistry and Astrobiology, especially those related to Biology, will enable students to access the forefront of this field of science.